Association between abdominal separation and inguinal or crural hernias: Our experience and surgical indications. Issue 3 (June 2013) - Dessy, Luca Andrea; Mazzocchi, Marco; Fallico, Nefer; Anniboletti, Tommaso; Scuderi, Nicolò
Abstract Abdominal wall weaknesses present several causative factors, both local and systemic and, as a consequence, abdominal hernias may develop in more than one site. Also, simultaneous hernia repair has been rarely reported in published reports. In the present study, the association of multiple weaknesses of the abdominal wall in patients undergoing conventional abdominoplasty or hernia repair were evaluated, and the advantages of simultaneous repair in a single operation are discussed. In a 3-year time period, all patients undergoing abdominoplasty or abdominal hernia repair were clinically and instrumentally evaluated for the association between median abdominal wall weakness and inguinal and/or crural hernias. The body mass index (BMI) was also considered and photographic documentation was taken before the operation and during the follow-up. When this association was confirmed, patients underwent contemporary correction of both conditions using an abdominoplasty approach. The presence of inguinal and/or crural hernias was observed in 10% of all patients undergoing conventional abdominoplasty and in 14.5% of patients with laparocele in the institution. The BMI was higher in patients with the association than in those without. Good aesthetic and functional results were achieved and the complication rate was low. The role of obesity as a triggering factor of abdominal wall weaknesses is confirmed by the higher BMI in patients with associated diseases. These observations remark the fact that the association between median abdominal wall weakness and inguinal or crural hernias should always be investigated. If this association is confirmed, it is preferable to treat both conditions simultaneously.